A pediatric view on pregnancy among adolescents: a bibliographical study (Revista Latino-Americana de Enfermagem, 2002)
This study analyzes the content of the scientific production of three national pediatric journals from 1990 to 1999, concerning pregnancy among adolescents and identifies the justifications for this occurrence and the follow-up suggested. The following variables were investigated according to their frequency: journal; year of publication; authors background; keywords; ideas associated with the subject in question; methodology. A qualitative approach enabled an analysis of the pediatric explanations and recommendations concerning this theme. Among 1437 papers, only 1.1% were related to the subject. Controversies regarding the importance of the biological risk involving the adolescents' lives were observed in the papers. In sum, the authors point out the need for an interdisciplinary perspective in approaching this theme, considering the complexity of the aspects involved in the pregnancy among adolescents.